2022
DOI: 10.5114/pjr.2022.112466
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low dose and ultra-low dose on the visibility of peri-implant fenestration and dehiscences: a computed tomography study

Abstract: Purpose This study aimed to evaluate the visibility of peri-implant fenestration and dehiscences on computed tomography (CT) images taken with 2 different doses. Material and methods The defects were created on the apical of 6 implants randomly selected from 20 titanium implants placed in the ribs, and dehiscences were created on the cervical of 8 implants. No defects were created around 6 implants. Macroscopic analysis of the implanted ribs was accepted as the gold sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Also, in a study conducted by Schriber et al [ 40 ] no difference was found between low-dose and high-dose protocols in the detection of buccal peri-implant dehiscence defects. Our results were in line with the results of Aktuna-Belgin et al [ 41 ] who evaluated the efficiency of two different CBCT doses (low dose and ultra-low dose) in the detection of peri-implant fenestration and dehiscence defects, and they found that the diagnostic accuracy was not affected in the two protocols used.…”
Section: Discussionsupporting
confidence: 92%
“…Also, in a study conducted by Schriber et al [ 40 ] no difference was found between low-dose and high-dose protocols in the detection of buccal peri-implant dehiscence defects. Our results were in line with the results of Aktuna-Belgin et al [ 41 ] who evaluated the efficiency of two different CBCT doses (low dose and ultra-low dose) in the detection of peri-implant fenestration and dehiscence defects, and they found that the diagnostic accuracy was not affected in the two protocols used.…”
Section: Discussionsupporting
confidence: 92%
“…[39], no difference was found between low-dose and high-dose protocols in the detection of buccal peri-implant dehiscence defects. Our results were in line with the results of Aktuna-Belgin et al [40], who evaluated the e ciency of two different CBCT doses (low dose and ultra-low dose) in the detection of peri-implant fenestration and dehiscence defects, and they found that the diagnostic accuracy was not affected in the two protocols used.…”
Section: Discussionsupporting
confidence: 92%